Determination of void fraction in wet-gas vertical flows via differential pressure measurement. (March 2022) - Tait, Paul; Chen, Yuan; Senjyu, Wataru; Watanabe, Toru; Inamura, Yasuo; Presotto, Valentina; Mojsak, Radek; Chinello, Gabriele; Jia, Jiabin
Abstract: The measurement of void fraction in multiphase flow is important for a wide range of industrial processes. Existing methods for void fraction measurement require intrusive, expensive and potentially hazardous equipments which constrict the flow, adding both capital and operational costs. Two phase flow experiments were carried out at the National Engineering Laboratory (NEL) to measure void fraction via pressure drop in a vertical pipe. Additional experiments are carried out at Spirax Sarco Inc. to validate the efficacy of the method on steam/water flow mixtures at high temperature and pressure, in gas mass fraction range between 0.17 and 0.95 and void fraction range between 0.75 and 1.0. The void fraction calculated by the presented differential pressure (dP) method is confirmed via established correlations. The work demonstrates the efficacy of a low cost, non-intrusive method to determine void fraction in two phase flow over a wide range of flow conditions. Highlights: A novel non-intrusive, low cost void fraction measurement sensor is described. Measurements based on Bernoulli's principle are made on vertical 2-phase flows. Results are confirmed against 2 established correlations for void fraction. Performance of measurements can be enhanced by including frictional effects.